DIABETES MANAGEMENT IN CHRONIC KIDNEY DISEASE: A COMPREHENSIVE SYSTEMATIC REVIEW - Sijabat, Landong; Novettiandari, Guinanti (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The increase in type 2 diabetes has positioned it as the leading cause of chronic kidney disease (CKD) and is responsible for approximately half of all cases of end-stage kidney disease (ESKD) worldwide. Managing CKD in diabetic patients entails addressing its complications and minimizing the risk of other associated conditions, such as cardiovascular disease. This study aims to serve a comprehensive systematic review on diabetes management in CKD patients in literatures of the last 10 years. Methods: The systematic review followed PRISMA 2020 standards and examined full-text English literature published between 2014 and 2024. This review excluded editorials, review papers from the same journal, and submissions without a DOI. Literature was sourced from online platforms such as PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  43,740   articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, four articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Chronic kidney disease (CKD) is a common and serious complication in individuals with diabetes. Management involves controlling hypertension and hyperglycemia, along with using ACE inhibitors like finerenone and SGLT2 inhibitors such as dapagliflozin, sotagliflozin, and bexagliflozin.